Acute toxicity and "structure-action" dependence of 4-(R-benzylidenamino)-5-methyl-4H-1,2,4-triazoles 3-tion - T. V. Kravchenko; Ye. S. Pruglo; O. I. Panasenko; E. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The achievements of modern pharmaceutical chemistry allow to develop a wide range of potential new drugs. However, their success in clinical practice depends on their safety. Therefore, the presence of evidence of their safety and efficacy is an integral part of any research.